Geriatric Rheumatology A Comprehensive Approach - Nakasato, Yuri; Yung, Raymond L. (Springer New York : Imprint: Springer, 2011)
The first book dedicated explicitly to the care of elderly patients with rheumatic diseases, this comprehensive resource is a practical guide for navigating the medical concerns of these complex patients.  While patients over 65 years of age comprise roughly 15% of the population, they consume about 50% of rheumatology resources.  This book presents current clinical practices with an eye toward achieving economically sustainable models of care.  The world's leading authorities have come together to cover the full spectrum of rheumatic diseases, the immune system in aging, and ultrasound evaluation and arthrocentesis.  The book also addresses the milieu of co-morbidities that the clinician may encounter with an older patient, as well as the accompanying concerns about multiple pharmacologic therapies and drug interactions.  Bringing in experts from a wide array of subspecialties, the editors present the essentials of multidisciplinary care, an approach which is the hallmark of geriatrics and which naturally translates into the field of gerontorheumatology.  Designed for primary care physicians and rheumatology consultants, Geriatric Rheumatology is an invaluable guide to caring for this rapidly growing patient population.